The Role Of Work Environment And Employee Engagement On Employee Performance In The Private Sector Of Makassar City - Abdul Haris S; Erwina (International Journal of Education Management and Religion, 2026)
This study aims to analyze the influence of work environment and employee engagement on the performance of private sector employees in Makassar City. The research was conducted in Makassar City among employees working in private companies operating in service, trade, banking, and other business sectors. The sample consisted of 77 respondents. The sampling technique employed was purposive sampling with specific predetermined criteria. This study utilized quantitative data. Data collection was conducted through observation, interviews, and questionnaire distribution. The collected data were subsequently analyzed using multiple linear regression analysis to test the research hypotheses. The results indicate that simultaneously, work environment and employee engagement have a significant and positive influence on the performance of private sector employees in Makassar City. Partially, work environment has a significant and positive effect on the performance of private sector employees in Makassar City. Employee engagement does not have a significant impact on the performance of private sector employees in Makassar City.